Modeling and Rescue of the Vascular Phenotype of Williams‐Beuren Syndrome in Patient Induced Pluripotent Stem Cells. (21st December 2012) - Kinnear, Caroline; Chang, Wing Y.; Khattak, Shahryar; Hinek, Aleksander; Thompson, Tadeo; de Carvalho Rodrigues, Deivid; Kennedy, Karen; Mahmut, Naila; Pasceri, Peter; Stanford, William L.; Ellis, James; Mital, Seema
Abstract : The objective of this study was to generate a human induced pluripotent stem cell model for in vitro assessment of the Williams‐Beuren syndrome (WBS) phenotype and to test the ability of candidate agents to rescue the phenotype. It was found that the abnormal smooth muscle phenotype associated with WBS could be reproduced in vitro in smooth muscle cells derived from reprogrammed skin fibroblasts from a WBS patient. This study provides a valuable in vitro platform to model a genetic disorder associated with smooth muscle proliferation and vascular abnormalities and to test the in vitro efficacy of drugs that act downstream of the defective gene. Abstract : Elastin haploinsufficiency in Williams‐Beuren syndrome (WBS) leads to increased vascular smooth muscle cell (SMC) proliferation and stenoses. Our objective was to generate a human induced pluripotent stem (hiPS) cell model for in vitro assessment of the WBS phenotype and to test the ability of candidate agents to rescue the phenotype. hiPS cells were reprogrammed from skin fibroblasts of a WBS patient with aortic and pulmonary stenosis and healthy control BJ fibroblasts using four‐factor retrovirus reprogramming and were differentiated into SMCs. Differentiated SMCs were treated with synthetic elastin‐binding protein ligand 2 (EBPL2) (20 μg/ml) or the antiproliferative drug rapamycin (100 nM) for 5 days. We generated four WBS induced pluripotent stem (iPS) cell lines that expressed pluripotency genes and differentiated into all three germ layers. Directed differentiation of BJ iPS cells yielded an 85%–92% pure SMC population that expressed differentiated SMC markers, were functionally contractile, and formed tube‐like structures on three‐dimensional gel assay. Unlike BJ iPS cells, WBS iPS cells generated immature SMCs that were highly proliferative, showed lower expression of differentiated SMC markers, reduced response to the vasoactive agonists, carbachol and endothelin‐1, impaired vascular tube formation, and reduced calcium flux. EBPL2 partially rescued and rapamycin fully rescued the abnormal SMC phenotype by decreasing the smooth muscle proliferation rate and enhancing differentiation and tube formation. WBS iPS cell‐derived SMCs demonstrate an immature proliferative phenotype with reduced functional and contractile properties, thereby recapitulating the human disease phenotype. The ability of rapamycin to rescue the phenotype provides an attractive therapeutic candidate for patients with WBS and vascular stenoses.